Transient Release of Oxygenated Volatile Organic Compounds during Light-Dark Transitions in Grey Poplar Leaves - Graus, Martin (American Society of Plant Biologists, 2004)
In this study, we investigated the prompt release of acetaldehyde and other oxygenated volatile organic compounds (VOCs) from leaves of Grey poplar [Populus x canescens (Aiton) Smith] following light-dark transitions. Mass scans utilizing the extremely fast and sensitive proton transfer reaction-mass spectrometry technique revealed the following temporal pattern after light-dark transitions: hexenal was emitted first, followed by acetaldehyde and other C(6)-VOCs. Under anoxic conditions, acetaldehyde was the only compound released after switching off the light. This clearly indicated that hexenal and other C(6)-VOCs were released from the lipoxygenase reaction taking place during light-dark transitions under aerobic conditions. Experiments with enzyme inhibitors that artificially increased cytosolic pyruvate demonstrated that the acetaldehyde burst after light-dark transition could not be explained by the recently suggested pyruvate overflow mechanism. The simulation of light fleck situations in the canopy by exposing leaves to alternating light-dark and dark-light transitions or fast changes from high to low photosynthetic photon flux density showed that this process is of minor importance for acetaldehyde emission into the Earth's atmosphere.